Routine Use of Preoperative Neck Ultrasound in Primary Hyperparathyroidism Identifies Coexisting Thyroid Disease and Improves Parathyroid Localization. Issue 2 (February 2022) - Foster, Trenton; Dy, Benzon; Rocco, Raffaele; Mckenzie, Travis; Thompson, Geoffrey; Wermers, Robert; Lyden, Melanie
Background: In Jan 2018, we began routinely obtaining neck ultrasound (US) with 123I/99Tc-sestamibi (MIBI) for parathyroid gland localization and to identify thyroid pathology in the setting of primary hyperparathyroidism (1HPT). The aim of this study is to assess if routine neck US is a useful adjunct to 123I/99Tc-MIBI in 1HPT. Methods: Patients undergoing surgery for 1HPT with both 123I/99Tc-MIBI and US at our institution after implementation of routine US were reviewed. Biopsy and surgical management of thyroid pathology was evaluated. 123I/99Tc-MIBI and US results were compared to intraoperative findings to determine sensitivity and positive predictive value (PPV) for parathyroid localization. Results: From January 2018 to September 2019, there were 423 patients (mean, 61 years) that met inclusion criteria (80% women). Thyroid nodules were found on US in 57%, mean size 1.3 + 0.8 cm. Fine needle aspiration (FNA) was performed in 87 patients with nodules (36%). 35 patients (8.5%) required total or partial thyroidectomy for diagnoses/treatment. Papillary thyroid cancer (PTC) was found in 3.5% of the cohort with micro-PTC 53% and PTC 1-2 cm 40%. A successful parathyroid operation for 1HPT was achieved in 98.6% of patients. Positive predictive value for localization of abnormal parathyroid glands was 97% when US and 123I/99Tc-MIBI had concordant findings. Discussion: Routine use of US in 1HPT commonly identifies nodules that are benign or low-risk PTC. Ultrasound is less sensitive for parathyroid localization but when used with 123I/99Tc-MIBI, concordant imaging has a high PPV.